A study on the ecological quality of housing environments: Cypriot settlements - Oktay, D (Wit Press, 2003)
Since an understanding and an appreciation of ecology is central to the discipline of landscape architecture, implementing policies for ecological development would not simply mean the sensitive location of urban development in relation to landscape features. Of equal importance is respect for the ecological function of green spaces. In the context of housing, which seems to act as a container of changing circumstances, where individuals and groups play an important role in the creation of their habitats, ecological development deals with improving the quality of life of the local community through the prudent use of local resources. The aim, therefore, is for a high degree of local self-sufficiency, which is related to the ecological site design. Acknowledging these ideas, this paper, reviewing the literature in the field, firstly discusses the role of green spaces on the ecological quality of housing environments, and secondly evaluates the green spaces of Cypriot settlements by highlighting the typical characteristics of the older settlements which provide valuable clues for the ecologically sensitive developments.
4th International Conference on Ecosystems and Sustainable Development -- JUN 04-06, 2003 -- SIENA, ITALY